Eine neue Wandkarte der Klimagebiete der Erde nach W. Köppens Klassifikation - Geiger, Rudolf; Pohl, Wolfgang (ERDKUNDE, 1954)
The purpose of this paper is to outline the principles which were used for the new edition of a wall map, scale 1 : 16 millions, of the climates of the world according to Köppen’s classification. Published by Justus Perthes Verlag, Darmstadt, Donnersbergring 14, this multicoloured map is based on the latest availabe data calculated to a larger map scale than the first edition of 1928. Compared with that edition several improvements have been incorporated in contents as well as in appearance. Well balanced colouring makes the map more legible and a better impression of the relative size of areas is conveyed by the use of Winkel’s instead of Mercator’s projection. The most extensive changes are to be found in the desert and steppe regions which, formerly underestimated, cover large parts of the oceans. Important and in some cases surprising improvements have also been achieved in Asia and Africa. A small, generalized reproduction of the new map in black and white is enclosed.